The paratumoral immune cell signature reveals the potential for the implementation of immunotherapy in esophageal carcinoma patients - Strizova, Zuzana; Snajdauf, Martin; Stakheev, Dmitry; Taborska, Pavla; Vachtenheim, Jiri; Biskup, Jan; Lischke, Robert; Bartunkova, Jirina; Smrz, Daniel (Journal of cancer research and clinical oncology, 2020)
PURPOSE: Esophageal cancer (EC) is one of the most lethal gastrointestinal malignancies. Immunotherapy is a promising treatment modality for this disease. However, broader implementation of EC immunotherapy has been discouraged because of insufficient understanding of tumor interactions with the immune system. As with other malignancies, the current research on EC focuses on deciphering the immune cell signatures within the tumor microenvironment. However, the disease-elicited immune cell profiles in the paratumoral compartments are largely unknown. METHODS: We examined the immune cell signatures in 62 tissue samples from 16 EC patients in different esophageal tissue compartments: tumor tissue, peritumoral tissue, healthy esophageal tissue, and adjacent lymph nodes. We analyzed the proportions and distribution patterns of NK cells and CD4+ and CD8+ T cells as well as their death receptor (FasR, FasR/DR3)-expressing subpopulations. The analyzed data were then compared and correlated with the patients' clinicopathological data. RESULTS: We found that the FasR+ NK cells, CD4+ and CD8+ T cells infiltrated lymph nodes at the lowest levels and that the FasR+DR3+ CD4+ T cells were enhanced in tumors. The comparisons with the clinicopathological data revealed a major impact of active smoking on the reduction in paratumoral NK cells and the upregulation of FasR in tumor-infiltrating NK and CD8+ T cells. The lymph node metastatic stage, tumor stage, and Mandard grade correlated with the compartmental proportions of the evaluated immune cells. CONCLUSION: The novel association of the disease state with tumoral and paratumoral immune cell signatures suggests new possibilities for personalized immunotherapy for EC patients.
Keywords: tumor infiltrující lymfocyty; Female; lymfocyty; skvamózní karcinom jícnu; ženské pohlaví; Mandard tumor regression grade; Lymphocytes, Tumor-Infiltrating; buňky NK; Esophageal cancer; lymfatické uzliny; Immunotherapy; lidé; Esophageal Neoplasms; CD8-Positive T-Lymphocytes; Death receptor 3; studie případů a kontrol; antigeny CD95; nádory jícnu; Humans; Tumor-infiltrating lymphocytes; T-lymfocyty - podskupiny; Adenocarcinoma; Male; CD8-pozitivní T-lymfocyty; imunoterapie; Aged; Case-Control Studies; Killer Cells, Natural; Peritumoral lymphocytes; adenokarcinom; fas Receptor; Esophageal Squamous Cell Carcinoma; Lymph Nodes; Lymphocytes; lidé středního věku; CD4-Positive T-Lymphocytes; senioři; mužské pohlaví; T-Lymphocyte Subsets; Fas receptor; Middle Aged; CD4-pozitivní T-lymfocyty